2018
DOI: 10.1007/s13239-018-0352-3
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Characterisation of Bovine Embolus Analogues Under Various Loading Conditions

Abstract: Embolus Analogues (EAs) can provide understanding of the mechanical characteristics of blood clots of cardiac origin. Bovine EAs (n = 29) were fabricated with varying concentrations of thrombin (0-20 NIHU/ml blood). Histological staining confirmed that EA composition compared sufficiently with human samples reported in literature. EAs were mechanically described under seven testing conditions: tensile, compression, shear wave ultrasound elastography (SWE), parallel plate rheometry, indentation, creep and relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 25 publications
3
20
0
Order By: Relevance
“…The clot analogues were found to have a similar, non-linear stress-strain relationship and mechanical behaviour to published data for clot material 5 7 8 22. The NCCs were found to be less stiff than the PCCs across all hematocrits.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The clot analogues were found to have a similar, non-linear stress-strain relationship and mechanical behaviour to published data for clot material 5 7 8 22. The NCCs were found to be less stiff than the PCCs across all hematocrits.…”
Section: Discussionsupporting
confidence: 57%
“…MT procedures are significantly affected by the mechanical properties of the thrombus itself. Clinically relevant thrombus analogues provide a useful tool in the preclinical testing of thrombectomy devices to evaluate device design by measuring, among other things: the ability to capture and remove the occlusive thrombus, the number of attempts required, and the risk of procedure related embolism 4–8…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated clot hyperelastic and viscoelastic behaviour using compression testing [27][28][29][30] and tensile testing [18,[31][32][33][34]. However, no study to date has investigated the fracture properties of blood clots.…”
Section: Introductionmentioning
confidence: 99%
“…34 Ovine, porcine and bovine blood is the most frequently used mammalian blood for EA replication. 17,26,3538 Bovine blood was chosen for EA manufacture as the supply was in close proximity to the laboratory (Burkes Abattoir Ltd, Galway, Ireland) and also, on a macro level, the composition of bovine blood is similar to human. 39…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of the blood clots (Figure 1(f)) were validated by in-house methods. 26 The bovine blood clots (n = 29) were described under seven loading conditions: tensile, compression, shear wave ultrasound elastography (SWE), parallel plate rheometry, indentation, creep and relaxation. The EAs displayed a compressive Young’s modulus varying from 1.53–16.6 kPa for a percentage strain range of 5%–40%, which was similar to other compressive studies found for human retrieved emboli.…”
Section: Methodsmentioning
confidence: 99%